2011
DOI: 10.1097/sla.0b013e318211d7d8
|View full text |Cite
|
Sign up to set email alerts
|

Survival With the Native Liver After Laparoscopic Versus Conventional Kasai Portoenterostomy in Infants With Biliary Atresia

Abstract: This prospective study shows that the laparoscopic Kasai procedure for biliary atresia is technically feasible. However, the study was stopped after inclusion of 12 laparoscopically operated infants due to a lower survival with the native liver after laparoscopic versus conventional Kasai operation. Superior results after conventional operation were confirmed at follow-up after 24 months. Study registration ID: EBAR 9260/NCT01063699.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(44 citation statements)
references
References 0 publications
2
42
0
Order By: Relevance
“…In 2011, Ure et al reported a prospective study that demonstrated that this approach is indeed technically feasible, but the study was stopped after inclusion of 12 infants subjected to a laparoscopic Kasai, due to a significant lower survival with the native liver compared to children treated by its laparotomic counterpart. 53 Another study failed to detect any benefit of laparoscopic compared with conventional HPE, in particular no lower incidence of adhesion formation hence easier subsequent LT, one of the intended goals of the laparoscopic approach. 54 If the Kasai operation succeeds, bile flow is restored, the stools become colored, and jaundice fades.…”
Section: Laparotomy Versus Laparoscopy Hpementioning
confidence: 99%
“…In 2011, Ure et al reported a prospective study that demonstrated that this approach is indeed technically feasible, but the study was stopped after inclusion of 12 infants subjected to a laparoscopic Kasai, due to a significant lower survival with the native liver compared to children treated by its laparotomic counterpart. 53 Another study failed to detect any benefit of laparoscopic compared with conventional HPE, in particular no lower incidence of adhesion formation hence easier subsequent LT, one of the intended goals of the laparoscopic approach. 54 If the Kasai operation succeeds, bile flow is restored, the stools become colored, and jaundice fades.…”
Section: Laparotomy Versus Laparoscopy Hpementioning
confidence: 99%
“…119 With the widespread application of minimally invasive techniques even to the most complex operations, the laparoscopic Kasai procedure has been described and used at several centers worldwide. [120][121][122] Most reports, however, involve single cases or small series of carefully selected patients. A recent prospective trial confirmed the feasibility of the operation but revealed a significantly poorer outcome at 6 and 24 months, causing the trial to be stopped.…”
Section: Surgical Controversiesmentioning
confidence: 99%
“…A recent prospective trial confirmed the feasibility of the operation but revealed a significantly poorer outcome at 6 and 24 months, causing the trial to be stopped. 122 Outcomes of other series have been variable 123 and, therefore, the laparoscopic Kasai procedure currently lacks support among general pediatric surgeons including those who specialize in minimally invasive pediatric surgery. Some investigators have proposed that primary liver transplant be considered the initial treatment for infants with biliary atresia, citing deleterious effects of the Kasai procedure on possible subsequent liver transplant.…”
Section: Surgical Controversiesmentioning
confidence: 99%
“…Laparoscopic porto-enterostomy (Kasai's Procedure) for biliary atresia is performed in a similar fashion and has been first described by Esteves et al in 2002 (45) and small case series have been published since. a prospective trial comparing open and laparoscopic Kasai's procedure from our institution had to be stopped because of a significantly higher rate of early liver failure associated with the laparoscopic procedure (46). Due to the poor outcome, laparoscopic porto-enterostomy can not be generally recommended at present.…”
Section: Laparoscopic Duodeno-duodenostomy and Malrotationmentioning
confidence: 99%